THE EFFECT OF THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE BERINGIN DISTRICT OFFICE OF DELI SERDANG REGENCY - Fatimah Pohan; Rahimah Angkat (Jurnal Ilmiah Teunuleh, 2022)
Beringin District is one of the sub-districts in Deli Serdang Regency, has a Vision of "The realization of excellent service in Bringin District with Reliable Human Resource Support". This institution has the tagline that your satisfaction is our pride. But in its implementation there are still many obstacles that occur in the field so that it can hinder the desire of leaders in the sub-district in realizing that staff/employees can work effectively and efficiently. The purpose of this study is (1) To find out the condition of the work environment at the Beringin District Office of Deli Serdang Regency. (2) To find out the performance of employees at the Beringin District Office of Deli Serdang Regency. (3) To find out whether there is a significant influence between the work environment on the performance of employees in the Beringin District Office of Deli Serdang Regency. This research is quantitative research using simple regression analysis. The results showed that the work environment of the Beringin District Office of Deli Serdang Regency fell into the category of very good. The performance of employees of the Beringin District Office of Deli Serdang Regency falls into the category of very good. There is no positive and significant influence between the work environment and the performance of employees in the Beringin District Office of Deli Serdang Regency and those indicated by the correlation coefficient value (r) of 0.224 and the coefficient of determination (r2) of 0.05.